Application of the Pancasila Student Profile - H. Abdul Kadir (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The curriculum is a reference in determining the goals to be achieved in the world of education, both at RA, SD/MI, SMP/MTs, SMA/MA and even at the tertiary level. The Merdeka Curriculum is a continuation of ideas from thinkers from the world of education and even studies from educators, in the Merdaka Curriculum, the project raises the profile of Pancasila. The Pancasila student profile project in its sense is a step to strengthen Pancasila values proclaimed by the Minister of Education and Culture with the target context for students by determining an attainment of Graduation Standards (SKL) that have been determined for each level of education, in the independent curriculum. instilled character that is integrated with Pancasila norms. The task as an educator in charge of the world of education as a mandate-bearer is to make students become educators who have the character according to the mandate of the national education goals to form people who believe and fear God Almighty, have noble character for the nation and homeland that beloved